Prophylactic Cefazolin in Amnioinfusions Administered for Meconium-Stained Amniotic Fluid - R. K. Edwards; P. Duff (Hindawi Limited, 1999)
Objective: To determine if amnioinfusion with an antibiotic solution decreased the rate of clinical chorioamnionitis and puerperal endometritis in patients with meconium-stained amniotic fluid.